2022
DOI: 10.1038/s41598-022-21711-5
|View full text |Cite
|
Sign up to set email alerts
|

The NOGO receptor NgR2, a novel αVβ3 integrin effector, induces neuroendocrine differentiation in prostate cancer

Abstract: Androgen deprivation therapies aimed to target prostate cancer (PrCa) are only partially successful given the occurrence of neuroendocrine PrCa (NEPrCa), a highly aggressive and highly metastatic form of PrCa, for which there is no effective therapeutic approach. Our group has demonstrated that while absent in prostate adenocarcinoma, the αVβ3 integrin expression is increased during PrCa progression toward NEPrCa. Here, we show a novel pathway activated by αVβ3 that promotes NE differentiation (NED). This nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 62 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…We have previously shown that high levels of αVβ3 increase the expression of NgR2, a novel αVβ3 binding partner and NE marker regulator in PrCa cells [ 34 ]. To further investigate whether NgR2 affects cell attachment to αVβ3 ligands, we used adhesion assays [ 34 ]. First, we tested the expression of the following epitopes of αVβ3: LIBS1, 2 and 6.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that high levels of αVβ3 increase the expression of NgR2, a novel αVβ3 binding partner and NE marker regulator in PrCa cells [ 34 ]. To further investigate whether NgR2 affects cell attachment to αVβ3 ligands, we used adhesion assays [ 34 ]. First, we tested the expression of the following epitopes of αVβ3: LIBS1, 2 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple datasets show increased levels of RTN4RL2 (the gene encoding NgR2) RNA in advanced PrCa patients [ 34 ], the role of NgR2 in NE cancer progression was not explored before our paper was published [ 34 ] and had never been analyzed in sEVs. Because NEPrCa is characterized by late diagnosis, based on metastatic biopsy in patients with spread aggressive disease with low or absent PSA levels [ 69 ], NgR2 may represent a promising, specific marker for a non-invasive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations